THE TRANSFORMATION OF SUSPICION: NARRATIVE INSTABILITY AND THE COLLAPSE OF LEGAL AUTHORITY IN A KILLER WITHIN (2004) - Kusumajanti, Wahju; Wahyuningsih, Mirotin Eka; Kudriavtseva, Irina (Universitas Negeri Surabaya, 2026)
device into a structural condition that destabilizes legal authority and epistemological certainty in the detective genre. Departing from the classic convention that positions investigation as a means of restoring order, the film reverses this structure by positioning the protagonist, Addison Terrill, as both suspect and investigator. This study uses a qualitative approach through textual analysis within a narrative theory framework, specifically focalization, detective structure, and the representation of institutional authority. The results show that the film reconfigures the detective paradigm through the blurring of the boundaries between suspect and investigator, the fragmentation of focalization that limits access to knowledge, and the representation of legal institutions as structures that are not fully trustworthy. Suspicion no longer functions as a path to truth but instead circulates continuously and produces narrative instability. Furthermore, the deconstruction of the domestic space reinforces the collapse of the social order and the protagonist's identity. Thus, the film does not offer a restoration of order. It constructs a narrative world in which certainty is never fully achieved and authority is constantly questioned, reflecting a shift in contemporary crime cinema towards exploring uncertainty as a structural principle.